1975
DOI: 10.1021/j100577a005
|View full text |Cite
|
Sign up to set email alerts
|

Chemistry of silica supported chromium ions. I. Characterization of the samples

Abstract: Publication costs assisted by Italian CNRA definite compound is formed between CrOs and SiOg, the predominant surface structures being dichromates. By reduction in CO of the surface phase, Cr11 is mainly obtained. The activity of the reduced samples toward CO and ethylene polymerization is affected by chromium concentration and thermal treatments, both high Cr contents and high reduction temperatures decreasing the specific activity. The most active catalysts are characterized by Cr loading <0.5% and reduction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
106
0
2

Year Published

1996
1996
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 175 publications
(110 citation statements)
references
References 7 publications
2
106
0
2
Order By: Relevance
“…The UV-Vis DRS spectra for the lowest Cr loading exhibited two bands dominating at 348 and 240 nm with a shoulder at 429 nm, and the corresponding Raman spectra contained just one band at 895 cm -1 . These spectral features indicate hydrated surface dichromate species [7,10]. As the Cr loading was further increased, the UV-Vis bands broadened and shifted from 348 to 370 nm, and the shoulder at 429 nm became more pronounced.…”
Section: Hydrated Supported Cro X /Sio 2 In Initial Oxidizedmentioning
confidence: 95%
See 1 more Smart Citation
“…The UV-Vis DRS spectra for the lowest Cr loading exhibited two bands dominating at 348 and 240 nm with a shoulder at 429 nm, and the corresponding Raman spectra contained just one band at 895 cm -1 . These spectral features indicate hydrated surface dichromate species [7,10]. As the Cr loading was further increased, the UV-Vis bands broadened and shifted from 348 to 370 nm, and the shoulder at 429 nm became more pronounced.…”
Section: Hydrated Supported Cro X /Sio 2 In Initial Oxidizedmentioning
confidence: 95%
“…1. [10]. The IR spectra exhibited a broad band at 925 cm -1 that was assigned to surface dichromate sites on silica.…”
Section: Hydrated Supported Cro X /Sio 2 In Initial Oxidizedmentioning
confidence: 98%
“…In general, three oxidation states, Cr DRS spectroscopy 48,[56][57][58] show the presence of three new species: (pseudo-) octahedral Cr 2+ , (pseudo-) tetrahedral Cr 2+ , and (pseudo-) octahedral Cr 3+ , their relative concentration depending on the treatment and the support composition. The spectroscopic fingerprints of these reduced Cr species are summarized in Table 2.…”
Section: Reduced Crmentioning
confidence: 99%
“…However, the results from this approach were contradictory. Hogan [8,9] and McDaniel [17± 20] concluded that CrO 3 attaches mainly as monochromate, while Zecchina et al [14] and Krauss and Stach [22] reported that dichromate was the dominant species. Others have tried to correlate the geometry of chromate and dichromate with models of amorphous supports [2,3].…”
Section: Calcined Catalystmentioning
confidence: 99%